Implementasi Sistem Pakar Dengan Metode Forward Chaining Untuk Diagnosa Penyakit Kulit Anjing - Jayadinanta, Ida Putu Ari; Suhartana, I Ketut Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2023)
Dogs are humans' favorite pets because of the various advantages possessed by these animals. If you have a disease, usually the owner of the dog will throw it away for various reasons, such as lack of knowledge about dog diseases and the limited presence of veterinary clinics. One of the common diseases suffered by dogs is skin disease. The research stages started from Literature Study, Data Collection, System Development (CLI), and Results. The source of knowledge of this expert system for diagnosing dog skin diseases consists of types of dog diseases and their symptoms obtained from information sources on Literature Studies/Libraries available on the internet. The results of the implementation are the CLI System Start Page, the Confirmation Page for Starting Diagnosis, the Diagnosis Page, the Diagnosis Results Page, and the Confirmation Page for Performing the Diagnosis Again. This expert system is expected to help dog owners to diagnose diseases based on visible symptoms.